Dividends and earnings quality: Evidence from India. Issue 2 (June 2020) - Mulchandani, Kalyani; Mulchandani, Ketan; Wasan, Pratibha
Abstract: The objective of this study is to determine the association between dividend payment and earnings quality. Four features of dividends have been examined in the study–dividend paying status, size of dividends, changes in dividends and dividend persistence. The sample consists of 107 companies listed on S&P BSE200 and, for analysis, 12 years, that is, 2004 to 2015, are considered. Multiple regression analysis is used for analysis. It is evident that dividends convey information about a firm's earning quality. Payment of dividends, changes in dividends and dividend persistence communicate information about quality of earnings, but size of dividend does not have a significant relation with earnings quality.